Applying High Order Thinking Skill (Hots) on Teaching Reading Skills for The X Grade Students of SMAN 2 Kalukku - Mada Ali, Syahban; Hasanah, Nurul; Rosdiah (Inspiring: English Education Journal, 2022)
The aim of this research was to find out whether or not the students’ reading ability improved through High Order Thinking Skill (HOTS) for the X grade students of SMAN 2 Kalukku. The method was used was quantitative method. The instrument used to collect the data was reading test. The number of test consisted of 15 and the form is multiple choices. The population of this research was the grade of X students of SMAN 2 Kalukku. The number of the population was 119. The sample of this research was X IPS 1, the number of the students was 27. In analyzing the data collected through quantitative analysis. The result of this research was the applying of HOTS can improved the students’ reading ability for the X grade students of SMAN 2 Kalukku. It is supported by the result of the test which given for the students after given treatment. The result showed that there was an enhancement significantly between pre-test and post-test. The mean score of pre-test is 64.59 while post-test is 83.00. The result of the t-test analysis is 16.883 than t-table value was 2.056. It showed that the t-test value was greater than the t-table value (16.883 > 2.056). Keywords: High Order Thinking Skill (HOTS), Quantitative research, and Reading Skills